The impact of climate change on publich health: exploring the link to pharmacological knowledge and education - Al-Amin, Abul Quasem; Alam, Gazi Mahabubul; Othman, Abdul Jalil (Asian Network for Scientific Information, 2011)
The overall current of impact of climate change on public health, its general awareness and mapping of national policy is widely recognized. Nevertheless, some fundamental aspects have also remained underappreciated such as the impact of climatic change on plant biology, impacts of well-being of human in the ecosystem and knowledge-education in exploring the links to pharmacology. Therefore, we aim to address some of these issues linked, particularly feasible links between plant function and human health and present a list of key questions that may help to integrate plant biology into current paradigm on climate change and human health in the pharmacology. Here, we provide a number of critical examples that range over various health concerns related to plant biology and climate change and focus their inter-linkage of toxicology, aerobiology, contact dermatitis and pharmacology in exploring the system knowledge in plant biology. As the links among climate change, plant biology and public health that remain underappreciated by both plant scientist and health care providers; therefore, we present the degree of health risk posed by climate change and way forward to minimize adverse impacts.